Intercooperação cooperativa ou relação de subordinação? Estudo das relações Coamo e Credicoamo - Presa, Rosecleia Burei (2019)
Cooperativism emerged as an organizational form of resistance to capitalism, has been molding and adapting itself as a way of survival to the market throughout history. The cooperative model, which has as principles the organization and participation of the staff in its decisions, ends up incorporating capitalist strategies. Between these economic and social changes, many strategies adopted show us a distance by some cooperatives, their historical emergence as a social organization, mutual aid and equal participation. In this new organizational context, which combines the dissemination of financial capital in agriculture through the promotion and incentive of the agribusiness production model, which fosters the concentration and centralization of possessions and income, some cooperative groups are presented. The practice of intercooperation between cooperatives offers relevant organizational advantages, strengthening them, minimizing or supplying deficiencies among the participants. It happens, however, some aspects that characterize intercooperation do not converge with the capitalist logic of acting in the market, being more similar to the conglomeration that sometimes can constitute a conglomeration kind of financial capital. In this context, this study aims to identify the types of founding relationships developed by Cooperativa Agropecuária Mourãoense - Coamo, which is currently called Coamo Agroindustrial Cooperativa and its Credit Cooperative, Credicoamo. The main goal of this study was to investigate how the cooperative model developed and operated by Credicoamo - Crédito Rural Cooperativa and Coamo - Agroindustrial Cooperativa is founded, aiming to identify whether the prevailing practices are more similar to the principle of intercooperation or to the conglomeration of the type of financial capital. Using bibliographic and documentary research, 16 semi-structured interviews and 5 questionnaires through Likert-type scales, this research comprised its study from March 2018 to November 2019. The gathering , analysis and construction of the experienced context and built by the cooperatives, it was carried out through the method of dialectical historical materialism. Therefore, Coamo is known as materializing the actions of the State in favor of modernizing Brazilian agriculture, founded in 1970. Years later, it constitutes its credit cooperative, Credicoamo. This emerges as an integral part of a project for the resurgence of financial cooperatives, which integrates the credit cooperative with the agricultural cooperative. In this interconnected model, the actions are convergent and add to themselves to the promotion of Brazilian agribusiness, through the transfer of public agricultural and livestock resources subsidized by the State. Among the survival strategies are the adoption of administrative measures aimed at technical and economic efficiency. In this intertwining of actions, other companies emerge, which, added to the cooperatives, constitute a cooperative group, which, facing the need for survival, adopt a posture closer to the expansion business management with a view to profitability, moving away from the principles of cooperativism.